Motives for choosing growth-enhancing hormone treatment in adolescents with idiopathic short stature: a questionnaire and structured interview study - Huisman Jaap; Kamp Gerdine A; Geenen Rinie; Visser - van Balen Hanneke; Wit Jan M; Sinnema Gerben (BMC, 2005)
Abstract Background Growth-enhancing hormone treatment is considered a possible intervention in short but otherwise healthy adolescents. Although height gain is an obvious measure for evaluating hormone treatment, this may not be the ultimate goal for the person, but rather a means to reach other goals such as the amelioration of current height-related psychosocial problems or the enhancement of future prospects in life and society. The aim of our study was to clarify the motives of adolescents and their parents when choosing to participate in a growth-enhancing trial combining growth hormone and puberty-delaying hormone treatment. Methods Participants were early pubertal adolescents (25 girls, 13 boys) aged from 11 to 13 years (mean age 11.5 years) with a height standard deviation score (SDS) ranging from -1.03 to -3.43. All had been classified as idiopathic short stature or persistent short stature born small for the gestational age (intrauterine growth retardation) on the basis of a height SDS below -2, or had a height SDS between -1 and -2 and a predicted adult height SDS below -2. The adolescents and their parents completed questionnaires and a structured interview on the presence of height-related stressors, parental worries about their child's behavior and future prospects, problems in psychosocial functioning, and treatment expectations. Questionnaire scores were compared to norms of the general Dutch population. Results The adolescents reported normal psychosocial functioning and highly positive expectations of the treatment in terms of height gain, whereas the parents reported that their children encountered some behavioral problems (being anxious/depressed, and social and attention problems) and height-related stressors (being teased and juvenilized). About 40% of the parents were worried about their children's future prospects for finding a spouse or job. The motives of the adolescents and their parents exhibited rather different profiles. The most prevalent parental worries related to the current or future functioning of their children, while a few cases were characterized by no observed motives or by psychosocial problems only reported by the adolescents themselves. Conclusion The motives for participating in a growth-enhancing hormone trial are more obvious in the parents than in the adolescents themselves. Two out of three parents report worries about the future opportunities or observe modest current psychosocial problems in their children. The adolescents want to gain height, but the motivation underlying this remains unclear. Few of the adolescents experience psychosocial problems. Our analyses revealed differences among individuals in terms of motives, which implies that in an evaluation of hormone treatment, the importance of divergent outcome variables will also differ among individuals. Effectiveness evaluations of hormone treatment to increase height and the consequential fulfillment of other goals must be awaited.